PERAN MAHASISWA KKN DALAM EDUKASI DAN PENGELOLAAN TAMAN TOGA DI SEKOLAH DASAR NEGERI 010052 SEI KAMAH I - Deddy Wahyudin Purba; Safruddin Safruddin; Lokot Ridwan Batu Bara; Herviza Wulandari Pane; Heru Gunawan; Nurul utami; Muhammad Wahyu Wijaya; Devin Juanda; Muhammad Adzi Kurniawan (Smart Education, 2025)
Abstract: Community Service Program (KKN) is a community service program conducted by students that aims to make a real contribution to the development of community knowledge and skills. One form of KKN activity is the introduction and maintenance of Family Medicinal Plant Gardens (TOGA) in elementary schools. This activity aims to describe the role of KKN students in increasing students' and teachers' understanding of the benefits of TOGA and encouraging their sustainable maintenance. The methods used include socialization, planting practices, routine maintenance, and mentoring for school officials. The results of the activity showed an increase in students' understanding of the types of medicinal plants and their health benefits, along with basic skills in plant care. Teachers and school officials also gained additional insights into maintaining the sustainability of TOGA gardens as a learning and greening facility. Thus, KKN students act as educational agents and motivators in supporting the creation of a healthy, beautiful, and educational school environment.Â Keyword: KKN Students; Education; TOGA Garden; Elementary School.Â Abstrak: Kuliah Kerja Nyata (KKN) merupakan program pengabdian masyarakat oleh mahasiswa yang bertujuan memberikan kontribusi nyata dalam pembangunan pengetahuan dan keterampilan masyarakat. Salah satu bentuk kegiatan KKN adalah pengenalan dan pemeliharaan Taman Tanaman Obat Keluarga (TOGA) di sekolah dasar. Kegiatan ini bertujuan untuk mendeskripsikan peran mahasiswa KKN dalam meningkatkan pemahaman siswa dan guru mengenai manfaat TOGA serta mendorong keberlanjutan pemeliharaannya. Metode yang digunakan meliputi sosialisasi, praktik penanaman, perawatan rutin, dan pendampingan bagi pihak sekolah. Hasil kegiatan menunjukkan peningkatan pemahaman siswa mengenai jenis-jenis tanaman obat serta manfaatnya bagi kesehatan, disertai keterampilan dasar dalam perawatan tanaman. Guru dan pihak sekolah juga memperoleh wawasan tambahan untuk menjaga keberlanjutan taman TOGA sebagai sarana pembelajaran dan penghijauan. Dengan demikian, mahasiswa KKN berperan sebagai agen edukasi sekaligus motivator dalam mendukung terciptanya lingkungan sekolah yang sehat, asri, dan edukatif.Â Kata kunci: Mahasiswa KKN; Edukasi; Taman TOGA; Sekolah Dasar.